Wheat technology toolkit catalogue: Clearinghouse technical report series 011 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2021)
This catalogue describes a series of technologies related to the modernization of wheat production in Africa. It is based on the combined efforts of the Project Platform for Agricultural Solutions (ProPAS), an information portal, and the Technologies for African Agricultural Transformation (TAAT), a large collaborative program that is deploying agricultural solutions across the continent. Both activities are addressing the imperative to better connect proven technologies to those who need them, but each undertakes this goal in a very different manner. Wheat is one of TAAT’s priority commodities because of its huge importance to food and nutritional security, and the need for reduced flour imports to Africa. It is also targeted as an agro-industrial crop for processing and trading on world markets. During its compilation, ProPAS has accumulated several technologies that specifically address this commodity and we have compiled them into a “technology toolkit” designed to advance understanding and encourage adoption and investment into the proven agricultural solutions that advance this crop